Molecular characterisation and pathotyping of recently isolated Newcastle disease virus isolates based on F protein’s cleavage site - Shahrestani, Kiarash Roohani; Ideris, Aini; Bejo, Mohd Hair; Tan, Sheau Wei; Yeap, Swee Keong; Rasoli, Mehdi; Jazayeri, Seyed Davoud; Goh, Su Hua; Omar, Abdul Rahman (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
Intensive vaccine programs have been implemented in many countries including Malaysia, but Newcastle disease virus (NDV) outbreaks have occurred, even in well-vaccinated farms. Hence, the present study was aimed to characterize five NDV isolates obtained from NDV vaccinated broiler farms in 2011 based on sequence and phylogenetic analysis of partial fusion gene. All the isolated NDV strains showed that they are categorized as velogenic NDV based on the presence of multi-basic protease cleavage sites, 112RRRKRF117. In addition, phylogenetic analysis showed that the isolates can classified under the genotype VII, subgenotype VIId.